Management of Locastra muscosalis Walker (Lepidoptera: Pyralidae) Using Certain Synthetic Insecticides and Physical Methods - Sharma, Ajay (Indian Forester, 2005)
The efficacy of three synthetic insecticides and three neem products was evaluated in the field for the control of Locastra muscosalisWalker (Lepidoptera: Pyralidae) affecting Pistacia integerrima Stew ex. Brandis trees growing in the campus of Dr. Y.S. Parmar University of Horticulture and Forestry Nauni, Solan (H.P.). Along with these insecticides, a physical practice of removing the egg masses was also evaluated as a control method. Removal of egg masses was found to be the most successful method in controlling this pest. Amont the various chemicals used Endosulfan 35EC (1.5ml/lt) was found to be the most effective followed by Monocrotophos 36SL (2.5ml/lt) and Chlorpyriphos 20EC (2.5ml/lt). The neem products used to control the pest were found to show negligible effect in controlling the pest population when compared with the synthetic insecticides.